Applying linear programming in evaluating employees in higher education: A case study - Radoslaw Ryńca; Yasmin Ziaeian (PLoS ONE, 2025)
In the past few decades, any type of organization, from factories to government organizations, the banking sector, or educational institutions concentrates on increasing profit margins. To achieve this, one of the key factors is to achieve maximum output with minimum resources (input). Therefore, having an optimal plan to apply the resources has become extremely important for organizations. One of the relevant resources is Human resources. This paper presents a mathematical model as an aid for optimizing human resources in the higher education sector. The model includes seven stages: 1) determining the availability of research and teaching staff, 2) evaluating the research and teaching staff from the perspective of different stakeholders, 3) determining the cost of the availability of research and teaching staff, 4) examining the motivated employees, 5) developing a staff ranking, 6) developing the mathematical model, and 7) implementing the mathematical model.